2022
DOI: 10.3389/fcvm.2022.991646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of race and ethnicity disparities in outcome studies of CYP2C19 genotype-guided antiplatelet therapy

Abstract: Dual antiplatelet therapy with a P2Y12 inhibitor (clopidogrel, prasugrel, or ticagrelor) and aspirin remains the standard of care for all patients undergoing percutaneous coronary intervention (PCI). It is well-established that patients carrying CYP2C19 no function alleles have impaired capacity to convert clopidogrel into its active metabolite and thus, are at higher risk of major adverse cardiovascular events (MACE). The metabolism and clinical effectiveness of prasugrel and ticagrelor are not affected by CY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 94 publications
0
27
0
Order By: Relevance
“…In addition, it is quite relevant to consider ethnicity when evaluating responsiveness to antiplatelet agents ( 11 , 23 ). In fact, the prevalence of loss-of-function alleles of the CYP2C19 isoform varies greatly among races ( 9 ), which has a huge impact on clopidogrel responsiveness. This investigation is, to the best of our knowledge, the first to specifically compare the antiplatelet efficacy of ticagrelor vs. clopidogrel in a Mediterranean Caucasian population with DM and provides a valid confirmation of the PD superiority of ticagrelor over clopidogrel irrespective of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is quite relevant to consider ethnicity when evaluating responsiveness to antiplatelet agents ( 11 , 23 ). In fact, the prevalence of loss-of-function alleles of the CYP2C19 isoform varies greatly among races ( 9 ), which has a huge impact on clopidogrel responsiveness. This investigation is, to the best of our knowledge, the first to specifically compare the antiplatelet efficacy of ticagrelor vs. clopidogrel in a Mediterranean Caucasian population with DM and provides a valid confirmation of the PD superiority of ticagrelor over clopidogrel irrespective of ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, clopidogrel is still widely used in real-life clinical practice as part of dual antiplatelet therapy (DAPT), e.g., in patients undergoing elective PCI or in those with stabilized symptoms after an ACS following a strategy of DAPT de-escalation. It is well established that clopidogrel has a large interindividual variability in response with genetic factors, such as polymorphisms of cytochrome P450 (CYP) isoforms (mainly CYP2C19), playing a key role in this phenomenon ( 9 , 10 ). Evidently, the prevalence of genetic polymorphisms may vary greatly among races and, therefore, it is relevant that pharmacodynamic (PD) investigations take into consideration ethnicity when evaluating antiplatelet agents.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important is the near absence of data in historically underrepresented patient populations. 120 RCTs of genotype-guided DAPT have largely been conducted in patients of European ancestry, who have comprised 66% or higher of trial populations (Table 2). Research in those of African ancestry is especially needed given the higher risk for atherothrombotic events after PCI in this population versus European ancestry patients 121,122 and evidence of greater use of clopidogrel compared with prasugrel or ticagrelor among minority populations.…”
Section: G Aps In the Liter Aturementioning
confidence: 99%
“…Several major gaps remain in the evidence for P2Y 12 inhibitor pharmacogenetics. One of the most important is the near absence of data in historically underrepresented patient populations 120 . RCTs of genotype‐guided DAPT have largely been conducted in patients of European ancestry, who have comprised 66% or higher of trial populations (Table 2).…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…In particular, an appropriately powered study comparing outcomes in Black IM/PMs treated with clopidogrel vs. alternative therapy is needed to better discern the benefit of genotype-guided therapy in this population. 38 Previous studies have demonstrated greater use of medications addressed in pharmacogenetic guidelines, including clopidogrel, among Black patients than those of other race groups. 28,39,40 These data suggest that Black patients may be especially at risk for poor outcomes if they do not receive pharmacogenetic testing and subsequent adjustment of their drug therapy regimen if warranted based on test results.…”
Section: Articlementioning
confidence: 99%